Suitability of dried chips of plantain, cocoyam, yam and cassava for the development of the larger grain borer, Prostephanus truncatus (Horn) (Coleoptera: Bostrichidae) - Isah, M.D.; Ayertey, J.N.; Boateng, B.A. (International Journal of Pure and Applied Sciences, 2009)
Laboratory studies were conducted to determine the suitability of dried chips of cassava, yam, plantain and cocoyam for the development of Prostephanus truncatus. Substrate acceptability, suitability and susceptibility for egg bioassay and development were investigated. The tests were conducted using 2 varieties of each of plantain (apantu, asamienu), cassava (biafra, bosomensia), yam (pona, takyiman) and cocoyam (red, white) dried chips, where 100-200 unsexed adults were introduced into 500g shelled maize stored in a 1 litrekilner jars and covered with a metal screen which were remove dafter 2 weeks, the synchronized F1 progeny obtained were used for the experiments. Thebeetle successfully completed its life cycle on plantain and cassava dried chips and alsoachieved marginal success on yam and cocoyam chips. The mean developmental periodsof the beetle were 36.3-36.8, 35.5-36, 40-40.5 and 40.5-41 days on the plantain, cassava, yam and cocoyam chips respectively. Mean number of eggs laid on the dried chips of plantain, cassava, and yam ranged from 23.7-32.3, 34.3-44 and 11.3-12.7 while only10.3-11.3 eggs were recorded on dried cocoyam chips. Similarly, higher numbers ofadults were recorded on the dried chips of plantain and cassava than were recorded onthe dried chips of cocoyam and yam. Furthermore, higher per cent weight loss and quantities of frass produced were recorded on the dried chips of plantain and cassava than could be found on cocoyam and yam. These findings suggest that in the absence of the most preferred host (maize), the beetle can subsist on other dried chips especially plantain and cassava. It also means that dried plantain chips which have hitherto not been known to support the development of the beetle can serve as a satisfactory host for P. truncatus.
Keywords: Prostephanus truncatus; Plantain; Cassava; Yam; Cocoyam; Substrate Preference; Substrate Susceptibility